Model creative art layanan penguasaan konten teknik sketsa untuk meningkatkan kemampuan memahami bacaan siswa di sekolah menengah atas - Fauza Rizki; Muhammad Nur Wangid (Journal of Counseling, Education and Society, 2024)
The purpose of the study is to analyze the efficacy of the creative art model, specifically through the implementation of sketching techniques within content mastery services, as a pedagogical strategy to augment students’ reading comprehension at An-Nizam Private High School. Mastery of reading comprehension constitutes a foundational competency that underpins academic success, necessitating the incorporation of innovative learning frameworks to bolster students’ involvement in the educational process. The present study employed a quantitative methodology characterized by a pre-test and post-test design. The participant population comprised students from grade X, with the sample being drawn from class X MIA. Data acquisition was conducted through reading comprehension assessments and subsequently analyzed utilizing the Wilcoxon test. The analytical results indicated a statistically significant enhancement in students’ performance, as evidenced by the post-test mean score (91) surpassing the pre-test mean score (81). These results substantiate that the creative art model, leveraging sketching techniques, significantly improves students’ comprehension of reading materials. The research underscores the critical importance of incorporating creative methodologies within guidance and counseling services to optimize educational outcomes.